WO3/TiO2 hierarchical nanostructures for electrochromic applications. (1st March 2021) - Dhandayuthapani, T.; Sivakumar, R.; Zheng, D.; Xu, H.; Ilangovan, R.; Sanjeeviraja, C.; Lin, J.
Abstract: In the present work, we report the low temperature preparation of WO3 /TiO2 films via a two step process by combining chemical bath deposition and nebulized spray deposition techniques. We investigate the influence of WO3 layer on the structural, compositional, morphological and electrochemical properties of TiO2 films. The deposition of WO3 nanoplates on the TiO2 layer effectively improves the current density of the TiO2 films. The electrochemical study of the annealed WO3 /TiO2 films showed a colouration efficiency of 128.3 cm 2 C −1, optical modulation (Δ T ) of 78%, reversibility of 77.2% and with a fast response of 6 s for colouration and bleaching, and importantly, exhibited an excellent durability for 1000 cycles. This enhancement is ascribed to the interconnected nanoplate bundles which accommodate more charges, facilitate faster charge transport and in particular, the complementarity of the WO3 –TiO2 layers, result in complement between each other, thus leading to efficient electrochromic performance. Highlights: WO3 /TiO2 nanoplate bundles were prepared by facile two step process. A remarkable enhancement in current density was observed in WO3 /TiO2 films. The heterostructure improved the reversibility as well as the stability of the films. The WO3 /TiO2 films showed a maximum colouration efficiency of 128.3 cm 2 C −1 .